2013
DOI: 10.1680/gmat.12.00009
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of lignin-based materials

Abstract: There is a need for renewable resources as a raw material for commodity polymers. Lignin is one of the most important natural biopolymers from renewable resources due to its suffi cient supply, robust material properties and the fact that its use does not compete with the food supply. Lignin has been investigated since the late 19th century, but its applications are limited due to poor processability, low reactivity and intrinsic heterogeneity depending on the plant source and isolation methods used. Current s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
113
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(115 citation statements)
references
References 234 publications
(249 reference statements)
0
113
0
2
Order By: Relevance
“…Many researchers have found that lignin-carbohydrate complexes are a good natural biodegradable material [10,11]. In addition, LCC contains hydrophobic rigid lignin blocks and hydrophilic flexible polysaccharide blocks, making lignin-carbohydrate complexes have good amphipathy, biocompatibility, and mechanical strength [12]. The lignin and carbohydrate blocks in the LCC copolymer not only have an ideal structure for biomaterials, but also have good compatibility with animal cells [13].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have found that lignin-carbohydrate complexes are a good natural biodegradable material [10,11]. In addition, LCC contains hydrophobic rigid lignin blocks and hydrophilic flexible polysaccharide blocks, making lignin-carbohydrate complexes have good amphipathy, biocompatibility, and mechanical strength [12]. The lignin and carbohydrate blocks in the LCC copolymer not only have an ideal structure for biomaterials, but also have good compatibility with animal cells [13].…”
Section: Introductionmentioning
confidence: 99%
“…It has become an issue of significant research interest both for understanding the fundamental factors contributing to recalcitrance and for material applications of lignin [30]. Conformational parameters, including the molecular weight distribution (MWD), degree of polymerization, and molecular size distribution, can help to understand how the lignin structure changes during the PWO reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The main high added-value applications of lignin can be categorized into three groups: power/fuel, macromolecules, and aromatics [11,14]. Among those applications, aromatics commodities that are derived from lignin such as BTX (benzene, toluene, and xylene), phenol, and vanillin, are expected to offer a significant market potential with an estimated market value of over $ 130 billion; moreover, pyrolysis technology has drawn attention to opportunities available for converting lignin into these high value-added products [11,15,16].…”
Section: Introductionmentioning
confidence: 99%